The most favourable mobile messaging apps among IIUM students - Azhar Amanullah, Ayn Nur Azhana; Mohamad Ali, Noor Azian (International Journal of Science and Research, 2014)
Mobile messaging applications is rapid adopted globally. They allow mobile users to send messages to individuals or groups for very minimal fee, even some are totally free as long as the smartphones are connected to internet. WhatsApp is one of the top mobile messaging applications among a handful number of applications that have entered the market. The goal of this paper is to investigate the most favourable mobile messaging apps among IIUM students and to provide a feature comparison between a few selected mobile messaging applications. Despite the obvious of being a free application, this paper intends to investigate the other factors causing the widespread adoption of this mobile application especially among students. An online survey was distributed to 52 students from IIUM by using Google Docs to validate which mobile messaging applications are mostly used. Keywords: Mobile messaging apps, mobile instant messaging, smartphones, SMS, WhatsApp, features, IIUM